Strengthening movement for men's health from the nursing consultation in a Basic Health Unit: an experience report (Research, Society and Development, 2022)
Objective: this research is an experience report on a nursing consultation focused on the attention of men in a Basic Health Unit, located in the city of Niterói, Rio de Janeiro, carried out by Nursing students of the 6th period, from the Fluminense Federal University. Method: experience report based on the description, observation and execution of the nursing consultation for the care of the male, carried out in a Basic Health Unit, in the morning of July 2022. Results: an active search was carried out for users who were at the unit for other services such as: accompanying wives in gestational consultations, acquiring medication or vaccinating children, in order to identify suspected cases early and obtain a quick response to adequately guide the application of control measures. The main doubts raised by the users were related to prostate cancer, sexually transmitted infections and other chronic diseases, which were attended by the nurses of the UBS during the activity. Conclusion: The experience report on the strengthening movement for men's health from the nursing consultation in a Basic Health Unit, allowed to understand and better serve the way of attention to men's health, through the active search within a Basic Unit of Health. It provided the visibility to understand the needs and guide the male audience on the importance of taking care of health. Likewise, it stimulated the dialogue between the professional and the patient through the nursing consultation with a view to strengthening a healthy life.